Pengaruh Profitabilitas, Aktiva Berwujud, Ukuran Perusahaan, Pertumbuhan dan Umur Perusahaan Terhadap Struktur Modal Perusahaan (Studi Empiris pada Perusahaan Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia) - Ade Banani; Rayhan Fidho Baghaskoro; Najmudin Najmudin (Bahtera Inovasi, 2020)
The purpose of this study was to analyze the effect of profitability, tangible assets, company size, company growth, and company age toward capital structure in the raw material producing industries listed on the Indonesia Stock Exchange for the period 2012-2016. This study analyzed 17 Property and Real Estate sectors listed on the Indonesia Stock Exchange in year 2013 - 2018 period. The analytical tools used are multiple linear regression and hypothesis testing using t test calculations. The results showed that profitability, company size, company growth and company age had a positive effect on capital structure, while tangible assets did not have a significant effect on capital structure.